2023
DOI: 10.1177/17446295221148791
|View full text |Cite
|
Sign up to set email alerts
|

“The change was as big as night and day”: Experiences of professors teaching students with intellectual disabilities

Abstract: Since the inception of the Higher Education Opportunity Act in 2008, there has been an increase in the number of post-secondary education institutions in the United States that have established inclusive postsecondary programs for individuals with intellectual disabilities to attend college and achieve higher levels of employment. Previous studies have investigated the development and outcomes of these programs, however, less has been explored related to professors' experiences and perceptions regarding this u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…One technique focuses on taking the time to develop a working knowledge of the students’ backgrounds and culture experience(s). This knowledge can then be utilized to make learning activities and assignments more culturally relevant, which in turn, can increase engagement, accessibility of content, and overall success, as perceived by the instructor (Watts, López, & Davis, 2023). Instructors have also reported hands-on learning activities and techniques facilitated more meaningful and relevant learning, built on students’ background knowledge and experiences.…”
Section: Time and The Classroom And Instructional System/processesmentioning
confidence: 99%
See 1 more Smart Citation
“…One technique focuses on taking the time to develop a working knowledge of the students’ backgrounds and culture experience(s). This knowledge can then be utilized to make learning activities and assignments more culturally relevant, which in turn, can increase engagement, accessibility of content, and overall success, as perceived by the instructor (Watts, López, & Davis, 2023). Instructors have also reported hands-on learning activities and techniques facilitated more meaningful and relevant learning, built on students’ background knowledge and experiences.…”
Section: Time and The Classroom And Instructional System/processesmentioning
confidence: 99%
“…Many barriers have been identified by instructors related to providing effective instruction for students with disabilities in PSE settings. Specific, time-related challenges have included the ability to obtain information on students' backgrounds and needs, training and preparation as effective and inclusive instructors, making teaching and course organization accessible, and developing knowledge and skills related to using new technology (Watts, López, & Davis, 2023). At the classroom-level, proactive training and planning can support the accessibility, engagement, and communication/ relationship-building, which can support the learning and overall success of individuals with disabilities in PSE settings Instructor Accessibility and Engagement.…”
Section: Time and The Classroom And Instructional System/processesmentioning
confidence: 99%
“…This study examines the regions with the most excellent rates of teacher certification as well as pupils' cognitive development and emotional/behavioural milestones. Watts et al (2023) demonstrated our ability to comprehend the perspectives and experiences of academics working with students with intellectual disabilities. Using Bronfenbrenner's bio ecological approach, Collins et al (2022) investigated how students' senses of self, competence, and pride develop in response to their experiences in the classroom and the wider world.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, legislative changes in favor of students with ID at university and the reported benefits of this experience have led to an increase in the number of these students, as their families and they themselves see university as a viable opportunity for them [ 22 , 32 ]. Students with ID have several reasons for enrolling in higher education programs, including perceived social benefits, a desire to improve their chances of finding and securing paid employment, and the opportunity to make new friends, especially friends without disabilities [ 19 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%